Chikungunya and Dengue Encephalitis: A Critical Narrative Review - Rajesh Verma; Rajarshi Chakraborty; Ankit Khetan (Annals of Indian Academy of Neurology, 2025)
Viral encephalitis is one of the leading presenting features of neurologic emergencies in tropical and subtropical areas. Chikungunya encephalitis (CE) and dengue encephalitis (DE) are important neurologic disorders of the central nervous system (CNS) with increased morbidity and mortality. This review discusses the pathogenesis, clinical features, diagnostic workup, and management of CE and DE, and provides insights into the vector-borne diseases with the help of literature obtained from clinical studies, reviews, and case series/reports. Chikungunya, as well as dengue viruses, are spread by the bite of Aedes aegypti and Aedes albopictus. The pathogenesis includes either direct invasion of the nervous system and/or immune-mediated CNS injury. It starts with fever, body aches/myalgia, and arthralgia (more in chikungunya) and may progress to encephalitis, if not treated properly during the initial stages. Laboratory investigations show leukopenia/thrombocytopenia, immunoglobulin M (serum and cerebrospinal fluid) positivity, and real-time polymerase chain reaction positivity. Brain imaging does not have any specific diagnostic clue. However, chikungunya has a predilection for the medulla oblongata, while dengue may affect the thalamus to show the classical double doughnut sign. Treatment is invariably medical, with adequate hydration and additional supportive care, although steroids and immunoglobulins have also been tried. CE and DE are critical vector-borne illnesses of CNS with guarded prognosis. The exact pathogenesis needs further research insights. A high index of clinical suspicion and aggressive management can lead to better outcomes. No specific therapy or immunization is available for CE or DE. However, these can be controlled by cleaning and eliminating all potential vector-breeding places.